POTENSI AREA BANK SAMPAH GUNA MENUNJANG PENERAPAN GREEN CONSTITUTION DI KOTA MANADO - Piet Hein Pusung; Sonny D.J. Mailangkay (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2021)
The current global issue in the world is waste management. Garbage is very worrying because it has a direct impact on the biotic and abiotic environment. In addition, waste has also contributed to non-natural disasters for humans. The entry of plastic elements in the human body through fish and food that is exposed to microplastics. Many ways have been developed in dealing with the waste problem. The way to solve the waste problem is to reduce waste from its source by sorting it from the source and managing it further into new products. Reducing waste from its source by sorting it and saving it in the Waste Bank is a promising breakthrough that can encourage people to actively participate in waste management while supporting the implementation of a green constitution in the future. The purpose of this research is to obtain a mapping of the distribution area of ​​waste banks in the city of Manado and its surroundings as a basis for supporting the implementation of the green constitution. The research data was obtained through research using existing mapping applications and carried out with the google search engine. The use of the google search engine in mapping waste banks is on the basis that this application is widely used in finding addresses by various users. The data were analyzed regarding the mapping of the position of waste banks in Indonesia which was found on the website of the Ministry of Environment and Forestry under the name of the national waste bank management information system. However, when it was focused on finding a special waste bank in the city of Manado, the smash application could show the location of the waste bank in Manado City. The results of further research indicate the mapping of the current position of the waste bank in the city of Manado, consisting of the center, suburbs and outside the city. Furthermore, the results of the comparison of the three waste banks resulted in a management method. It can be concluded that effective waste bank management is carried out through a strategy of implementing 3R (Reuse, Reduce, Recycle) in waste management at the source at the community level. The results of the mapping are expected to become the basis for developing a green constitution policy as a development model for waste bank management in the future.